What are the factors influencing nurses to neglect patients' autonomy and decision-making? - Raziyeh Beykmirza; Reza Negarandeh (Tehran University of Medical Sciences, 2017)
one of the dimensions of family-oriented care is enhancing the adequacy and empowerment of the family, and respecting their autonomy and decision-making in child care and treatment. The studies indicate that providing support and information for the parents in the hospital environment during child care, notifying parents about the treatment plan, educating them and using their participation are the most important needs of the parents. This requires the supportive educational relationship of personnel, especially nurses with parents (3). However, there are many situations in nursing care that, if nurses are unaware or negligent, this patient's fundamental right will be violated. In this article, we will examine these factors and the findings of the studies conducted in this area. The study of Beykmirza et al (2017) revealed that among the nursing ethical codes, the domain of respect for autonomy and decision making from the perspective of mothers with a child with cancer was at the most unfavorable level of performance. In this study, nurses also acknowledged that they presented poor performance in this domain (4). These findings support the results of other studies on the contentment of parents of children with cancer with giving them the right to make decisions (5, 6). The findings from these studies may indicate the nurses' lack of knowledge about patient rights and the need for values-based practice. The health system in Iran is mainly far from the concept of patient and family orientation and giving decision-making rights on the basis of sufficient information. This is due to several reasons, such as lack of sufficient information from health care professionals, including doctors and nurses, about patient rights, having a stereotypical view about the lack of preparedness and competency of families to obtain information, the lack of a caring communication between the patient's family and caregivers along with empathy and attempt for empowerment, the high workload of professionals and in turn, assigning less time to the functions that include the non-physical aspects of patient and his or her family, as well as the lack of familiarity with professional ethics.  It seems that most nurses' beliefs is that if they give the families of children with cancer the right to autonomy in treatment, health and nursing interventions, they may face the families' irrational decisions. So, respecting this right is overlooked (7, 8). From their point of views, for example, if the families are familiar with the side effects of drugs, even if that drug is helpful to the physician, they may refrain from continuing treatment with that medication. Perhaps this is also the reason for the weakness in nurses' performance in the area of patient education. A study by Bartholdson et al. (2015) in Sweden showed the most ethical issues in pediatric cancer care were due to the violation of the patient's right to autonomy, limitation in reflecting facts, how to decide on the process of treatment and palliative care. Given the different perspectives and cultures, the degree of collaboration between the treatment team, the child with cancer and her/his family is challenged (9). The results of the study of Rahmani et al. indicated that most patients believed that nurses were at a poor level in respecting their autonomy in terms of providing information to them and their participation in the therapeutic decision-making process. In addition, Sadeghi's study (2009), entitled "respecting autonomy during nursing care from the perspectives of adolescents admitted to children's hospitals affiliated to Tehran University of Medical Sciences in 2008 showed that 66.7 percent of adolescents believed that their autonomy was slightly respected, and only 4 percent of them stated that their autonomy was fully respected. In the similar studies, the lack of sufficient time, insufficient personnel, and lack of readiness and experience of nurses to provide illness-related information and to give the right to autonomy and decision making to the family, were suggested as three important factors in nurses' neglect in this regard (10, 11).